BENTUK TES TOEFL UNTUK MAHASISWA UNIVERSITAS KALTARA: STUDI KUALITATIF - Aries Utomo; Puardmi Damayanti (Jurnal Penelitian Humaniora, 2019)
TOEFL is one of the tests used to measure a person's level of English with three forms of tests, namely (1) listening comprehension, (2) structure and written expression, and (3) reading comprehension. In addition to being used as a requirement when applying for a job, the test is also used by students for the purpose of college or as a condition for graduation. However, there are several universities that do not carry out these tests, one of which is Kaltara University. This study aims to describe kinds of  TOEFL tests which are able to work by Kaltara University students. The research method used is qualitative. This study uses data collection techniques, namely: (1) observation, (2) interviews, and (3) document analysis. The data analysis techniques used are Miles and Huberman Models. The results of this study indicate that (1) the hardest test done by the students is listening, meanwhile the easiest test done is structure and written expression; and (2) the ability of Kaltara University students had an average TOEFL score, 460 which was categorized as a minimum standard. Therefore, there needs to be an increase in TOEFL scores for Kaltara University students.